HUBUNGAN TINGKAT KECUKUPAN ZAT GIZI MAKRO DAN STATUS GIZI ( IMT/U DAN HB ) DENGAN TINGKAT KEBUGARAN JASMANI SISWA MI AL-KHAIRIYAH LEBAK KELAPA KOTA CILEGON - Ihsan Fahroji; Suyatno Suyatno; Sri Achadi Nugraheni; Apoina Kartini (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Physical fitness is the ability or ability of the body to make adjustments to physical liberation granted to him without experiencing excessive fatigue. Each person requires good physical fitness in order to carry out activities effectively and efficiently. This study aims to determine the relationship between carbohydrate intake, protein intake, fat intake, BMI/U and Hb levels with physical fitness levels in MI AL-Khairiyah Lebak Kelapa students, Cilegon City. The research design used was cross sectional. The population is 395 students and the number of samples is 76 respondents who are carried out proportionally random sampling with the sample criteria aged 10-12 years. Data was collected through filling out a questionnaire and a series of tests. The results showed that there was no relationship between carbohydrate intake (p = 0.439), protein intake (p = 0.611), fat intake a (p = 0.223), BMI for age (p = 0.857) and physical fitness level, there was a significant relationship between Hemoglobin levels with physical fitness level (p = 0,031). It was concluded that there is no relationship between the level of micronutrient adequacy and BMI/U with the level of physical fitness. However, there are relationship between Hb levels and physical fitness levels.